Evaluation of the XVI dual registration tool for image-guided radiotherapy in prostate cancer. (June 2021) - Sousa, Filipa; Jourani, Younes; Van den Begin, Robbe; Otte, François-Xavier; Ridai, Sara; Desle, Maxime; Ferreira, Angela; Ahmimed, Radia; van Klink - de Goeij, Moniek C.M.; Van Gestel, Dirk
Highlights: The dual registration tool (DRT) aims to improve the accuracy by using two automatic image registrations sequentially; For prostate irradiation, DRT could be considered in combination with additional verification, as manual correction by the RTTs is less often needed after DRT than after chamfer matching; For prostate bed irradiation with matching on the pubic symphysis, the chamfer match together with additional verification of the RTTs remains the best choice, as it is fast and accurate. Abstract: Purpose: To compare the reliability and the required time for two cone-beam CT (CBCT) registration methods for prostate irradiation (PI) and prostate bed irradiation (PBI). Material and methods: Two-hundred treatment fractions (in 10 PI and 10 PBI patients) were reanalyzed, using two CBCT registration methods: (1) a combination of an automated chamfer matching (CM) with manual matching (MM), and (2) the automated XVI dual registration tool (DRT). Bland-Altman 95% Limits of Agreement (LoA) were used to assess agreement with manual registration by Radiation Oncologists. Results: All 95% LoA for CM + MM were ≤ 0.33 cm. For DRT, several 95% LoA were notably larger than the predefined clinical threshold of 0.3 cm: −0.47 to +0.25 cm (PI) and −0.36 to +0.23 cm (PBI) for the superior-inferior direction and −0.52 to +0.24 cm (PI) and −0.38 to +0.31 cm (PBI) for the anterior-posterior direction. For PI, the average time required was 33 s with CM + MM versus only 18 s with DRT ( p  = 0.002). For PBI, this was 13 versus 19 s, respectively ( p  = 0.16). Conclusion: For PI, DRT was significantly faster than CM + MM, but the accuracy is insufficient to use without manual verification. Therefore, manual verification is still warranted, but could offset the time benefit. For PBI, the CM + MM method was faster and more accurate.